The Impact of Emission GHG Performance on Financial Performance: Moderating by Financial Constraints and COVID-19 - Meliani Nababan; Sylvia Veronica Nalurita Purnama Siregar (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Previous studies on the relationship between GHG emissions and financial performance presented two competing points of view: either reducing GHG emissions can cause firms to diverge from their corporate goals, or, reducing GHG emissions can raise firm value in line with the resource-based view theory. This study examines 105 non-financial industry in Indonesia that produce significant amounts of emissions GHG between 2019 and 2021, with a total of 315 data observations. This study analyzes the financial performance using ROA and firm value, and the performance of GHG emissions using two constructs: the quantity of emissions and disclosure of GHG emissions. The Global Initiative Report (GRI) guidelines are used to conduct content analysis on disclosure of GHG emission. This study shows that GHG emission performance is considered as a firm's competitive advantage, there is a positive relationship between GHG emission performance and firm value, financial constraints negatively impact the relationships between GHG emission performance, and COVID-19 had no impact on the relationship between emission performance and financial performance.